2015
DOI: 10.1371/journal.pone.0132317
|View full text |Cite
|
Sign up to set email alerts
|

Long-Duration Spaceflight Increases Depth Ambiguity of Reversible Perspective Figures

Abstract: The objective of this study was to investigate depth perception in astronauts during and after spaceflight by studying their sensitivity to reversible perspective figures in which two-dimensional images could elicit two possible depth representations. Other ambiguous figures that did not give rise to a perception of illusory depth were used as controls. Six astronauts and 14 subjects were tested in the laboratory during three sessions for evaluating the variability of their responses in normal gravity. The six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 35 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…In spite of the importance of graviception on Earth for visuo-motor and other aspects of motor control, the astronauts’ performance remained relatively good in microgravity (refs 11,12,15, 16, 17 for a review). Non-specific factors, such as the noisy environment in the ISS, stress, muscle artifacts and basic physiological factors (differences in blood circulation in both the brain and the body as a whole), seem unlikely to be the source of the alpha ERD reinforcement here described, as we did not find any significant variation when exclusively analyzing the power spectrum changes during the baseline period1320.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the importance of graviception on Earth for visuo-motor and other aspects of motor control, the astronauts’ performance remained relatively good in microgravity (refs 11,12,15, 16, 17 for a review). Non-specific factors, such as the noisy environment in the ISS, stress, muscle artifacts and basic physiological factors (differences in blood circulation in both the brain and the body as a whole), seem unlikely to be the source of the alpha ERD reinforcement here described, as we did not find any significant variation when exclusively analyzing the power spectrum changes during the baseline period1320.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of weightlessness on the dynamic organization of the brain is a central issue for space neuroscience and has important implications for future long-term missions. It also helps clarify a number of issues in neuroscience11. Microgravity offers an environment where cognitive and sensorimotor functions are continuously challenged.…”
mentioning
confidence: 99%
“…The importance of spaceflight and exploration programs and the activities of astronauts in space have become increasingly recognized worldwide. To ensure the safety of space missions and astronauts, considerable research on spaceflight safety has been conducted . However, with the constant improvements to the reliability of complex systems, human error has become the most critical factor in reducing system reliability, which can potentially lead to mission failures or catastrophic accidents .…”
Section: Introductionmentioning
confidence: 99%
“…Less obvious are the effects of gravity on visual perception, where the notion of direct vestibular influences on the perception of retinal signals is not intuitive. Nevertheless, experiments on orbit and during parabolic flight have demonstrated the influence of gravitational cues on visual percepts such as the interpretation of ambiguous figures [ 28 , 29 ], the perception of object orientation [ 30 , 31 ] and the identification of an axis of symmetry [ 32 – 35 ]. Other studies have shown an influence of weightlessness on the perception of visual cues linked to whole-body motions [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown an influence of weightlessness on the perception of visual cues linked to whole-body motions [ 36 , 37 ]. Of particular interest to the question of object affordances are studies showing the effects of weightlessness on the perceived shape and size of visual objects [ 29 , 30 , 38 41 ]. Among them, changes in apparent dimensions of objects were found to take place in weightlessness, leading to underestimation of objects’ size and distance [ 42 45 ].…”
Section: Introductionmentioning
confidence: 99%